Effects of supplemental microbial phytase on performance of broiler chickens - Kiiskinen, Tuomo; Piironen, Jari; Hakonen, Tiina (Agricultural Research Centre of Finland, 1994)
Sienifytaasin (Aspergillus niger) lisäyksen vaikutusta broileripoikasten (0-5,5 vk) kasvuun, rehunkulutukseen, luuston mineraalisoitumiseen ja fosforin hyväksikäyttöön tutkittiin kolmessa kokeessa, joissa oli yhteensä 5100 poikasta. Soija-viljapohjainen perusrehu sisälsi lisättyä kivennäisfosforia 0-0,1 % (negatiivinen vertailurehu) entsyymilisäyksen ollessa 250-1000 fytaasiyksikköä (PU) rehugrammassa. Positiivisessa vertailurehussa kivennäisfosforin lisäys oli 0,24-0,30 %. Fytaasin lisääminen perusrehuun, jossa ei ollut lainkaan tai hyvin vähän (0,05 %) lisättyä kivennäisfosforia, lisäsi selvästi broilerien rehunkulutusta ja kasvua. Fytaasilisäyksellä 1000 PU/g saavutettiin sama kasvutulos kuin positiivisella vertailurehulla. Sääriluusta tehdyt mittaukset ja määritykset osoittivat, ettei fytaasilisäyksellä ollut merkittävää vaikutusta luun mineralisoitumiseen, jos rehuun lisättiin kivennäisfosforia. Ellei rehuun lisätty kivennäisfosforia fytaasilisäyksen vaikutus sääriluuarvoihin oli huomattava. Fytaasilisäys (1000 PU/g) paransi fosforin hyväksikäyttöä perusrehussa ja vähensi fosforin erittymistä ulosteista. Koetulosten mukaan kivennäisfosforin käyttöä voidaan huomattavasti vähentää broilerien rehuissa lisäämällä niihin fytaasia, jolloin myös lannassa eritetty fosfori vähenee.

Three trials were conducted on a total of 5100 broiler chicks (0-5.5 weeks) to study the effects of different microbial phytase (Aspergillus niger) supplementations (250-1000 phytase units = PU/g) on the performance and bone mineralization of birds and on the utilization of phosphorus compared with the effects of mineral P additions as dicalcium phosphate. The basal diets (negative controls) were principally composed of soya bean meal (SBM) and grain (wheat, barley, oats) supplemented with up to 0.10% mineral P; the positive control diets were supplemented with 0.24-0.30% mineral P. Compared with the negative control groups, which were fed diets with 0.05% mineral P either during the whole rearing period or during the starting period only, phytase addition increased live weight by 4-7% and feed intake by 3-9% (Trials 1 and 2). Tibia values indicated that with low mineral P supplementations (0.05 and 0.10%), phytase additions have a non-significant effect on bone mineralization. If mineral P is not added, the tibia values show a marked response to phytase (Trial 3). Utilization of P inereased from 50.9% to 60.0% when phytase (1000 PU/g) was added to the diets without mineral P supplementation (Trial 3). Utilization of P was only 34.5% in the positive control diet (0.3% mineral P). The results were obviously affected by the intrinsic phytase activity in grain and the dietary calcium level, and suggest that, in SBM-grain-based diets with very low (0.05%) or no mineral P supplementation, weight gain can he increased by adding phytase up to 1000 PU/g. This supplemented phytase activity is apparently sufficient for adequate bone mineralization.
Keywords: siipikarja; broilerit; rehu; fytaasi; phosporus; phytic acid; growth; feed efficiency; bone mineralization; mineral utilization